The effectiveness of car scrapping schemes in the Italian market - Romano, Antonio Angelo (Metodološki zvezki, 2012)
The aim of this work is to examine the effectiveness of policies in support of the automotive industry that have taken place over the years and the link between car registration and consumer confidence. Firstly, through an intervention analysis, the series of total car registrations in Italy has been corrected for the effect of seasonality and incentives. Secondly, a Structural Vector Auto Regression model has been estimated in order to evaluate the effectiveness of the relationship between car registrations and consumers' confidence. The results show that policies in support of the automotive industry are useful if granted during an increasing economic trend. Otherwise they have no effect on sales of new vehicles.
Keywords: Consumers; Potrošniki; Automobile industry; automotive industry; Avtomobilska industrija; Statistical methods; Statistične metode; Italija; Italy